Secondary victims' perceptions of justice : implications for forensic psychology - Bannister, Benjamin (2013)
An emerging area of study has begun to look at the perceptions of justice of the family and friends of crime victims – or, secondary victims. It is important to improve understanding of secondary victims’ experiences of justice, partly because knowledge about how they perceive justice may help forensic psychologists assist them more effectively. This research attempted to assess how well existing justice theories could account for secondary victims’ perceptions of justice, and also help determine what is important to them. Using the largely ignored group of secondary victims of non-sexual violent crime, the research consisted of two interrelated stages. In Stage One, qualitative analysis was used to determine the justice perceptions of 22 secondary victims. The findings revealed that a combination of principles from various theories of justice were present in secondary victims’ views. However, participants also endorsed unique aspects of victimisation that did not link directly to existing theories. Importantly, many participants made primary victim and offender outcome comparisons using seven variables. Three related to the primary victim and four related to the offender. A second stage of research involved 156 potential secondary victim participants drawn from the community. They responded to a scenario involving a victim of crime, in order to determine whether they considered the same seven variables identified in Stage One in deciding whether justice had been achieved for that victim. The results showed that participants considered these variables when making comparisons of outcomes, and did so irrespective of whether they felt justice had been achieved in the given scenario. Overall, the findings of the two stages of this research represented an important step towards a more comprehensive understanding of the justice experiences and perceptions of secondary victims of violent crime, and therefore have important implications for forensic psychologists working with this group